Enhancing mental well-being of undergraduates: establishing cut-off values and analyzing substitutive effects of physical activity on depression regulation - Ma, Yue; Gao, Yulin; Yang, Hui; Zhang, Yu; Ku, Yixuan (Frontiers in Psychology, 2024)
Abstract Objective: To analyze the influence of physical activity (PA), sleep, and sedentary behavior on subthreshold depression (StD) among undergraduates. Methods: This study involved 834 undergraduates and assess the impact of PA time, sleep, and sedentary behavior influence on depression. ROC analysis was used to determine the cut-off values for StD risk and isochronous substitution was applied to evaluate the effects of different activities on depression regulation. Results: Gender, age, and grade had no significant influence on depression among undergraduates (P > 0.05). However, students with sedentary behavior for exceeding 12.1 hours per day, and a Pittsburgh Sleep Quality Index score above 3.5 were at increased risk of subclinical depression. Additionally, the isochronous substitution of light intensity physical activity for other activity behaviors (sleep, sedentary behaviors, moderate and vigorous intensity physical activity) was statistically significant (P<0.05) in the 5 minutes and 10 minutes substitution models, demonstrating a positive effect in alleviating depression. Conclusion: The findings indicate that specific lifestyle factors are crucial determinants of subclinical depression among undergraduates, independent of demographic variables such as gender, age, and grade. High levels of sedentary behavior, and poor sleep quality significantly increase the risk of subclinical depression among undergraduates. Notably, light intensity physical activity plays a distinct role in StD regulation, as substituting it with more intense physical activities or improving sleep quality substantially reduces depression scores. Furthermore, the facilitation benefit was observed to increase as the substitution duration increased.